2014
DOI: 10.1152/japplphysiol.00557.2013
|View full text |Cite
|
Sign up to set email alerts
|

ACTN3genotype and modulation of skeletal muscle response to exercise in human subjects

Abstract: α-Actinin-3 is a Z-disc protein expressed only in type II muscle fibers. A polymorphism in the ACTN3 gene (R577X) results in lack of α-actinin-3 in XX genotype. The prevalence of the mutated X-allele is lower among power/sprint oriented athletes compared with controls, indicating that the lack of α-actinin-3 is detrimental in these sports, but a mechanistic link has not been established. Results from Actn3-knockout (KO) mouse model suggest that α-actinin-3 may affect muscle mass and muscle glycogen levels. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
31
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 58 publications
2
31
1
Order By: Relevance
“…It is noteworthy that the differences between results found in this study and those of literature may be related to differences in the age group studied, test protocols used, countries of origin and level of physical activity of participants 13,27 , and in the future it would be interesting to analyze whether there is variation in gene and protein expression of ACE and ACTN3 in different age groups and subjects with different levels of physical activity, despite the difficulty in obtaining the tissues in which these genes are expressed (kidneys and lungs for ACE and skeletal muscles for ACTN3), which would help in the understanding of our results. In addition, the number of individuals in our study, as well as in studies used for discussion, can be considered a limiting factor due to the importance of a large number of subjects in studies with population genetics.…”
Section: Discussioncontrasting
confidence: 89%
See 2 more Smart Citations
“…It is noteworthy that the differences between results found in this study and those of literature may be related to differences in the age group studied, test protocols used, countries of origin and level of physical activity of participants 13,27 , and in the future it would be interesting to analyze whether there is variation in gene and protein expression of ACE and ACTN3 in different age groups and subjects with different levels of physical activity, despite the difficulty in obtaining the tissues in which these genes are expressed (kidneys and lungs for ACE and skeletal muscles for ACTN3), which would help in the understanding of our results. In addition, the number of individuals in our study, as well as in studies used for discussion, can be considered a limiting factor due to the importance of a large number of subjects in studies with population genetics.…”
Section: Discussioncontrasting
confidence: 89%
“…Individuals who have the XX genotype have lack of ACTN3, while heterozygotes (RX genotype) have fewer amount of ACTN3, but no disease 10 . ACTN3 is found in fast-twitch fibers (type II), suggesting that R577X polymorphism is related to functionality, power and muscle strength 11 , as shown by Kim et al 12 , who found lower frequency of XX genotype for the ACTN3 gene in elite athletes compared with non-athletes and also by Norman et al 13 , who showed that individuals with XX genotype for the ACTN3 gene have lower signaling for metabolic pathways associated with hypertrophy and less use of muscle glycogen during exercise. Thus, those who express ACTN3 (RX or RR genotypes) have advantage in activities that require strength or muscle power, while those who do not express ACTN3 (XX genotype) have advantage in predominantly aerobic activities.…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…Previous studies have reported an association between the RR genotype of the ACTN3 R577X polymorphism and muscle power in elite athletes22 ) and ordinary people23 ) . In particular, the XX genotype is lower among power/sprint-oriented athletes than the RR genotype24 ) , and this finding is supported by the observation that individuals with the XX genotype show lower thigh muscle cross-sectional area than those with the RR and RX genotypes14 ) . However, considering the role of ACTN3 in skeletal muscle, and consequentially muscle strength and endurance, the present study surprisingly found no such relationship.…”
Section: Discussionmentioning
confidence: 77%
“…For example, expression of actinin3, titin, and desmin is increased compared with controls. Z-disc component actinin3 is strongly associated with improvements in sprint or endurance (72,73), whereas titin is also localized to the Z-disc, which mechanically couples sarcomeric contraction and stretching (74,75). Desmin is required for the tensile strength and integrity of myofibrils (76).…”
Section: Discussionmentioning
confidence: 99%